Smart Repair System (SRS) - Nurul Huda, Ramli (2023)
The main goal of this project is to develop an online data inventory system for IT Mines Expert Resources. This system allows the employees to have a good management system to manage the device problems of customers who come to the store. The Smart Repair system will also allow technicians and trainees to work quickly, especially when repairing damaged devices. Technicians will ensure students can handle device problems well and learn something to improve knowledge and add experience in device repair. The administrator is responsible for operating this system. This project uses Rapid Application Development (RAD) as a methodology that serves as a guideline for the development phase or process.